Magnetic Resonance Imaging (MRI) in the Comprehensive Evaluation of Pelvic Endometriosis: A Retrospective Study in a Tertiary Hospital - Thapa, Rossu; Lamichhane, Suman; Swar, Avishek; Bhusal, Amrit; Suwal, Sundar; Katwal, Shailendra; Ghimire, Prasoon (Annapurna Journal of Health Sciences, 2025)
Introduction: Endometriosis is the presence of endometrial-like tissue outside the uterus and is a leading cause of pelvic pain, dysmenorrhea, and infertility. Magnetic Resonance Imaging (MRI) is a valuable non-invasive diagnostic tool for evaluating pelvic endometriosis. The objective of this study was to evaluate the MRI findings of pelvic endometriosis as well as its prevalance. Methods: This retrospective study, conducted at Nepal APF Hospital from December 2022 to December 2024, among 54 cases of patients with MRI features of endometriosis. Study population included 54 female patients of reproductive age group referred for MRI examination due to various reasons and had imaging features suggestive of endometriosis and adenomyosis. Consecutive sampling was done of all female patients with MRI features of pelvic endometriosis. MRI features were documented and organ wise involvement was assessed. Results: Most of the patients with endometriosis were referred for evaluation of already diagnosed conditions. Pelvic pain as the major symptom for referral after it. The most common MRI finding was endometrioma in unilateral or bilateral ovaries, seen in 39 patients. Fallopian tube findings were seen in 17 cases in the form of hematosalpinx and hydrosalpinx. Uterine findings were seen in 35 patients with most cases (n=28) comprising of adenomyosis (focal or diffuse thickening of junctional zone), and scar endometriosis was seen in 2 patients. Conclusion: Endometriosis occurs primarily in women of reproductive age group, with pelvic pain being the common symptom. MRI is required for the better visualization of endometriosis in specific locations with accuracy which might be missed by other imaging tools.